ANALISIS USAHA PEMANFAATAN JERAMI PADI (Oriza sativa) YANG DIKOSUMSI DENGAN EFFEKTIVE MIKROORGANISME-4 (EM-4) TERHADAP PERTUMBUHAN DOMBA SUNGEI PUTIH JANTAN - Yohanes Sianturi (Universitas Sumatera Utara, 2012)
Abstrac: Analysis of the Rice Straw Utilization (Oriza sativa) with the addition of Effektive microorganism 4 (EM4) on growth of Sungei Putih Lamb. Guided by ARMYN HAKIM DAULAY and ZULFIKAR SIREGAR. The research conducted at the Faculty of Agriculture, Animal Biology Laboratory that began in September 2011 until January 2012. This study aims to determine the business value of the addition of EM4 on rice straw for sungei putih lamb. Method used is a Latin Square design with 4 treatments. Treatments are P0 (0 ml EM4), P1 (2 ml EM4), P2 (4 ml EM4), P3 (6 ml EM4). The results showed that the average profit / loss is highest at P3 of Rp -20.603, - and the lowest at P1 Rp -7.761, -. Average Benefit Cost Ratio (B/C) is highest in the P1 at 0.984 and 0.961 for the lowest in P3. Average Break Even Point (BEP) BEP consisting of the highest production rates at P3 of Rp 31.464, - and the lowest on the P1 of Rp 30.758, -. Average BEP highest production volume of 17,28 kg on P3 and P0 for the lowest at 16.87 kg. Mean Income Over Feed Cost (IOFC) was highest at P1 of Rp 13.439, - and the lowest at P3 of Rp 593-. The conclusion was that the addition of liquid Effektive probiotic microorganism 4 (EM4) on rice straw given a sungei putih lamb to level 6 ml not reduce the cost of feed and maintenance. Keywords: Business Analysis, Liquid Probiotics EM4, Sungei Putih Lamb